2017
DOI: 10.1590/1806-9282.63.11.978
|View full text |Cite
|
Sign up to set email alerts
|

What clinical, functional, and psychological factors before treatment are predictors of poor quality of life in cancer patients at the end of chemotherapy?

Abstract: Objective: To correlate physical activity level (PAL), functional capacity and psychological state with quality of life (QoL) in cancer patients undergoing chemotherapy (CT). Method: Observational cohort study. Patients (n=121) with any primary cancer site with indications of chemotherapy with palliative or curative intent were evaluated at three moments: 1) patient admission (week 0), before chemotherapy; 2) week 8; 3) end of CT. Data were collected regarding QoL, PAL, clinical data, functional capacity (shor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 24 publications
0
4
0
2
Order By: Relevance
“…The authors reported reduced cancer-related fatigue and improved functional independence of activities of daily living, as measured by the Barthel Index, after the supervised exercise program 27 . The studies by Pereira, Santos and Sarges 15 and Mangia et al 10 reported that the functional capacity assessed by the ECOG questionnaire and the STS can contribute to the elaboration of care plans for the oncologic patient care, being that by identifying the functionality, mea-sures are taken to prevent or reduce functional impairment and the risk of complications. However, in this study, no significant changes in functional capacity were observed after the physiotherapy intervention.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The authors reported reduced cancer-related fatigue and improved functional independence of activities of daily living, as measured by the Barthel Index, after the supervised exercise program 27 . The studies by Pereira, Santos and Sarges 15 and Mangia et al 10 reported that the functional capacity assessed by the ECOG questionnaire and the STS can contribute to the elaboration of care plans for the oncologic patient care, being that by identifying the functionality, mea-sures are taken to prevent or reduce functional impairment and the risk of complications. However, in this study, no significant changes in functional capacity were observed after the physiotherapy intervention.…”
Section: Discussionmentioning
confidence: 99%
“…The McGill Pain Questionnaire is a multidimensional instrument to measure pain by location, intensity, and its behavior considering the sensitive, affective, evaluative, and mixed dimensions 9 . It has reliability and good validity in cancer patients 8,10 . The International Physical Activity Questionnaire (IPAQ) considers walking activities, moderate and vigorous physical activity, and has been used in cancer patients 10 .…”
Section: Methodsmentioning
confidence: 98%
See 2 more Smart Citations
“…Os estudos que usaram exercícios aeróbicos de baixa e média intensidade também apresentaram benefícios da exercício físico em relação à melhora da QV (GOKAL et al, 2015;JENSEN et al, 2014;MANGIA et al, 2017), redução da sensação de fadiga (WART et al, 1025;REPKA, HAYWARD, 2018;VENI et al, 2018) e melhora da função muscular (LIMA et al, 2018;WART et al, 2018). Exercícios de baixa e média intensidade têm a vantagem de facilitar a adesão.…”
Section: De Acordo Comunclassified